Optimization of the Online Driver's License Program to Facilitate Public Services in Order to Increase Public Trust by the Traffic Unit of the Cirebon City Police Department - Aprilian, Rifkidimas (Advances in Police Science Research Journal, 2024)
This research was based on technology advanced which is increasing so fast. Therefore publics should have follows the development. Polresta Cirebon which, including in territory jurisdiction polda West Java has already begin using SIM Online program as technology for driving licenses Publication services. This research was used to get to know why public. Did not want to know use the it. In this research we should have known the meaning of this program, and the the competence of Satlantas Polresta Cirebon human resource. To offered Public services via SIM Online program. This research was done on February 2020 in Polresta Cirebon. This research use qualitative appreoach, for the next data collection technic with field studies method, interview, and document studies. This research using management theory, Publics Service theory, optimalist concept, SIM concept, and UU RI No. 22 in 2009 about LLAJ. This results of this program in Satuan Lalu Lintas Polresta Cirebon was proceed as optimal due to low education of member in charge. Also few facilities and intra structure are damaged, unequal knowledge of community about program facilities available with some program SIM Online. Based on this research, the opini of this innovation optimize the socialization for publics and the cooperation with bhabinkamtibmas, school, company, university, village officers, sub – districs, also social media when there is an age – old community to direct to use the facility program, send off Satlantas member who have not major education yet and haven’t has operator sertifications advice the public who fail to practise, also rebuild facilities and instructure.